Teachers' Opinions About Primary Reading and Writing Teaching in Regions Where Turkish is Not Spoken as Mother Tongue - Karaman, Hamdi; Yılar, Ömer (Fırat University, 2023)
This research aims to reveal in depth problems and solution proposals faced by classroom teachers in the teaching process of first reading and writing of students whose mother tongue is not Turkish. In conducting to this research, one of the qualitative research methods, situation study was used. The study group of the research consists of 30 classroom teachers who had taught first grade at least once. A semi-structured interview form was created to collect data. Interview forms consist of 17 questions, 4 of them are personal information. Content analysis was used in the analysis of qualitative data obtained through interview forms. As a result of the interviews, teachers' opinions were presented with three main themes. Accordingly, the prominent results are; not knowing Turkish enough by students, being low participation in kindergarten, reading comprehension problems, not expressing themselves by students, being inexperienced and impatient by teachers, not doing their homework and tasks or making mistakes by students, and being careless by families. As a solution to these problems, the teachers suggested that the curriculum should be more detailed and local, families should be included in education by raising awareness, and the Turkish language speaking should be encouraged by the family and the students.

Bu araştırma ana dili Türkçe olmayan öğrencilerin ilkokuma yazma öğretimi sürecinde sınıf öğretmenlerinin karşılaştıkları problemleri ve çözüm önerileri derinlemesine ortaya koymayı amaçlamıştır. Araştırmanın yürütülmesinde nitel araştırma yöntemlerinden durum çalışması kullanılmıştır. Araştırmanın çalışma grubunu en az bir kere birinci sınıf okutmuş olan 30 sınıf öğretmeni oluşturmuştur. Verilerin toplanması amacıyla yarı yapılandırılmış görüşme formu oluşturulmuştur. Görüşme formları 4’ü kişisel bilgiler olmak üzere toplam 17 sorudan oluşmuştur. Görüşme formları ile elde edilen nitel verilerin analizinde ise içerik analizi kullanılmıştır. Yapılan görüşmeler neticesinde öğretmen görüşleri üç ana tema etrafında sunulmuştur. Buna göre öne çıkan sonuçlar; öğrencilerin Türkçeyi yeterince bilmemesi, anasınıfına katılımın düşük olması, okuduğunu anlama problemleri, öğrencinin kendini ifade edememesi, öğretmenlerin tecrübesiz ve sabırsız olması, öğrencilerin verilen ödev ve görevleri yapmaması veya yanlış yapması ve ailelerin ilgisiz olmasıdır. Öğretmenler bu problemlere çözüm olarak ise öğretim programının daha detaylı ve yöresel olmasını, ailelerin bilinçlendirilerek eğitim öğretime dâhil edilmesini, aileye ve öğrenciye Türkçe konuşulmasının teşvik edilmesini önermişlerdir.
TÜRKÇENİN ANA DİLİ OLARAK KONUŞULMADIĞI BÖLGELERDE İLKOKUMA YAZMA ÖĞRETİMİ İLE İLGİLİ ÖĞRETMEN GÖRÜŞLERİ